mmWave 5G and SOTM system test automation and over the air testing (OTA) - Roy, Sanjucta (Nanyang Technological University, 2024)
The convergence of millimeter-wave (mmWave) technology and 5G networks has ushered in a new era of wireless communication, offering unprecedented data rates and low-latency connectivity. System-on-the-Move (SOTM) systems, designed for dynamic and mobile environments, leverage these advancements for applications ranging from autonomous vehicles to emergency response and military operations. These communication systems promise to support extremely high data rate, over 10 Gbps. To achieve such a challenging data rate at longer distance beamforming phase array systems are incorporated. This phased array system consists of a transmitter (Tx) and Receiver (Rx) with multiple channels each with variable gain attenuator (VGA) and phase shifters (PS). This complex system must work efficiently for a frequency range of 18 to 50 GHz for 5G and SOTM with high gain >10dB and a noise figure of below 2.2dB. Beamforming Integrated Circuits (BFICs) consist of these various components integrated on a single specialized chip. To verify these features and design, multiple tests are conducted. These tests include but are not limited to both individual and integrated IC component characterization, gain, phase, noise testing, and error calculation, multiple times over several samples to accommodate precision and accuracy. The rising demands call for faster test timing to focus more on analysis. Documenting the data is yet another factor to maintain the integrity of testing. Therefore, automating these tests can enhance the overall testing time, reduce errors, and optimize the analysis of these measurements. The dissertation aims to understand some of the essential mmWave tests and develop an algorithm to automate them using existing technology and reinforcement learning from manual testing, analysis and documentation. The GPIB interface has been used to connect the different testing equipments to a computer where we can deploy LABVIEW, MATLAB and Python environment to communicate with them and command them to proceed with RF tests. SCPI commands using VISA tool can also be deployed to communicate with these instruments. Since some algorithms are pre-existing, they have been optimized for re-use and optimized based on the first-hand learnings, scope and shortcomings of manual testing for specific RF tests. The automation algorithm has been developed, tested and verified for both testing, Major tests that have been studied include device linearity validating tests – power amplifier (PA) compression point (p1dB) testing and power-added efficiency (PAE%) testing, device noise measurements – Noise figure of Low Noise Amplifiers (LNA), device phase measurements- S parameter testing of PS and VGA components of Tx and Rx, active and passive component characterization, and OTA simulation using MATLAB Simulink 5G Toolbox. After this, the Key Performance Indicators (KPIs) have been analyzed to understand the behaviour of these devices. Algorithms have been developed to initiate automation and testing optimization wherever possible. The importance of these tests and the algorithm flowchart have been explained elaborately in this report. This dissertation has been undertaken in collaboration with the Institute of Microelectronics, ASTAR, in their Integrated Circuit Design and Systems laboratory. All manual measurements have been carried out in theiresteemed laboratory. The algorithms have been verified remotely using LabVIEW, MATLAB, Spyder tool, and VISA Toolkit. Keywords: 5G, SOTM, mmWave, phase array system, 1x1, transmitter, receiver, VGA, PS, BFIC, frequency range, gain, noise figure, RF test, simulation, automation, documentation, post-processing, LABVIEW, SCPI, Amplifier compression point, PAE%, Simulink 5G Toolbox, KPIs, VISA Toolkit.